Asymmetric Amine-Carboxylic Acid Organic-Inorganic Hybrid Wells Dawson Polyoxometalates - Alnahdi, Noor (2023)
Symmetric organofunctionalised polyoxometalates have been widely studied in recent years, due to their desirable characteristics, including catalytic properties and varied redox behaviour. However, limited research has been conducted into the design, synthesis and characterisation of asymmetric organofunctionalised hybrid POMs. These are of increasing interest because of their tunable electronic properties and ability to access precise functionality.